2014
DOI: 10.3988/jcn.2014.10.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Negative Variation Is Associated with Cognitive Dysfunction and Secondary Progressive Disease Course in Multiple Sclerosis

Abstract: Background and PurposeThe relationship between contingent negative variation (CNV), which is an event-related potential, and cognition in multiple sclerosis (MS) has not been examined previously. The primary objective of the present study was thus to determine the association between CNV and cognition in a sample of MS patients.MethodsThe subjects of this study comprised 66 MS patients [50 with relapsing-remitting MS (RRMS) and 16 with secondary progressive MS (SPMS)] and 40 matched healthy volunteers. A neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Later on, Uysal and colleagues [42] found that CNV has been well related to the activity of the prefrontal cortex and correlated with the psychological preparation activities of the person as attention, anticipation, arousal, motivation, memory, preparation, and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, Uysal and colleagues [42] found that CNV has been well related to the activity of the prefrontal cortex and correlated with the psychological preparation activities of the person as attention, anticipation, arousal, motivation, memory, preparation, and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CNV is an ERP that has been related to the activity of the prefrontal cortex and tells about the psychological preparation activities of the subject. It is well correlated with psychological activities such as anticipation, attention, arousal, memory, motivation, preparation, and decision (Uysal et al 2014 ). Thus, the findings of our NP study are somewhat aligned with the clinical study, highlighting the association of rather global cognitive dysfunction with IIH (Yri et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a cutoff for elevated CSF opening pressure needs to be specified (Friedman and Jacobson 2002 ). The event-related potential (ERP), P300, is involved in cognitive processing (Thakur et al 2011 ), whereas the contingent negative variation (CNV) is another ERP that is speculated to show awareness, attention, decision-making, planning, and conation, as well as readiness for a motor response (Uysal et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment is not rare in patients with epilepsy, due to different factors (the underlined pathology, side-effects from the pharmacotherapy, excessive cortical neuronal activity during ictal and interictal periods). There are reports that CNV may serve as a marker for disease progression and cognitive dysfunction in patients with multiple sclerosis (15). There are results showing differences in CNV amplitude between migraine patients and controls and these findings were used to follow the beta blockers treatment effects in migraine (16).…”
Section: Cnv Paradigm a Window To The Cognitive Functioningmentioning
confidence: 99%